Hepatitis B Virus Promotes Hepatocellular Carcinoma Progression Synergistically With Hepatic Stellate Cells via Facilitating the Expression and Secretion of ENPP2 - Deng, Wanyu; Chen, Fu; Zhou, Ziyu; Huang, Yipei; Lin, Junlong; Zhang, Fapeng; Xiao, Gang; Liu, Chaoqun; Liu, Chao; Xu, Leibo (Frontiers in Molecular Biosciences, 2021)
Background: Hepatitis B virus (HBV) infection is a major risk factor causing hepatocellular carcinoma (HCC) development, but the molecular mechanisms are not fully elucidated. It has been reported that virus infection induces ectonucleotide pyrophosphatase-phosphodiesterase 2 (ENPP2) expression, the latter participates in tumor progression. Therefore, the aim of the present study was to investigate whether HBV induced HCC malignancy via ENPP2. Methods: HCC patient clinical data were collected and prognosis was analyzed. Transient transfection and stable ectopic expression of the HBV genome were established in hepatoma cell lines. Immunohistochemical staining, RT-qPCR, western blot, and ELISA assays were used to detect the expression and secretion of ENPP2. Finally, CCK-8, colony formation, and migration assays as well as a subcutaneous xenograft mouse model were used to investigate the influence of HBV infection, ENPP2 expression, and activated hepatic stellate cells (aHSCs) on HCC progression in vitro and in vivo. Results: The data from cancer databases indicated that the level of ENPP2 was significant higher in HCC compared within normal liver tissues. Clinical relevance analysis using 158 HCC patients displayed that ENPP2 expression was positively correlated with poor overall survival and disease-free survival. Statistical analysis revealed that compared to HBV-negative HCC tissues, HBV-positive tissues expressed a higher level of ENPP2. In vitro, HBV upregulated ENPP2 expression and secretion in hepatoma cells and promoted hepatoma cell proliferation, colony formation, and migration via enhancement of ENPP2; downregulation of ENPP2 expression or inhibition of its function suppressed HCC progression. In addition, aHSCs strengthened hepatoma cell proliferation, migration in vitro, and promoted tumorigenesis synergistically with HBV in vivo; a loss-function assay further verified that ENPP2 is essential for HBV/aHSC-induced HCC progression. Conclusion: HBV enhanced the expression and secretion of ENPP2 in hepatoma cells, combined with aHSCs to promote HCC progression via ENPP2.